USEFULNESS AND SAFETY OF EARLY AGAINST DELAYED ORAL INTAKE AFTER APPENDECTOMY: Oral Intake After Appendectomy - Sheikh, Irfan Ali; Shukr, Irfan; Taj, Rizwan Ullah; Anwar, Muhammad Waseem (Pakistan Armed Forces Medical Journal, 2015)
Objective: To evaluate the usefulness and safety of early versus late oral intake after appendectomy.Study Design: Randomized clinical trial.Place and Duration of Study: Combined Military Hospital Multan from August 2008 to February 2009.Material and Methods: One hundred patients with uncomplicated acute appendicitis, undergoing appendectomy under general anesthesia were included in the study and randomly divided into two equal groups. Early oral intake group (group A) was allowed fluids, when patients were out of effects of general anesthesia. Delayed fed (group B) was started oral fluids, on appearance of normal bowel sounds or passage of flatus. Low residue solid diet was started, after tolerance of oral fluids, in both groups. Results: Early oral intake resulted in start of solid diet earlier by average 9 hours; these patients had normal bowel sounds, and passed flatus, earlier, after 4 hours and 5 hours as compared to late feeding group. Six (12%) patients had mild ileus in early fed group whereas 4(8%) patients in delayed fed group had mild ileus. Thirty eight (76%) early fed patients were very satisfied, as compared to 29 (58%) delayed fed patients. The hospital stay was prolonged by 2 days in delayed fed group.Conclusion: Early oral feeding implemented after appendectomy is safe and effective, with a shortened hospital stay as the primary benefit in patients after appendectomy.